Symmetries of ZN graded discrete integrable systems. (18th May 2020) - Fordy, Allan P; Xenitidis, Pavlos
Abstract: We recently introduced a class of Z N graded discrete Lax pairs and studied the associated discrete integrable systems (lattice equations). We discuss differential–difference equations which then we interpret as symmetries of the discrete systems. In particular, we present nonlocal symmetries which are associated with the 2D Toda lattice.